An Evaluation of Bera Lake (Malaysia) Sediment Contamination Using Sediment Quality Guidelines - Mohammadreza Gharibreza; Muhammad Aqeel Ashraf; Ismail Yusoff; John Kuna Raj (Journal of Chemistry)
Bera Lake is known as the first RAMSAR site and is the largest natural lake in Malaysia. Sediment quality guidelines (SQGs) and Geoaccumulation index were used to evaluate Bera Lake sediment contamination. Five undisturbed cores were collected from Bera Lake sediment. Major and trace levels of elements were determined for 132 subsamples using an inductively coupled plasma mass spectrometry (ICP-MS). The results marked two major groups of metallic elements bonded to the terrestrial and organic-rich sediments. Terrestrial sediments were strongly associated with accumulation of Li, Al, Pb, Cu, Cr, Na, Mg, Sr, and K during main fluxes of metals. However, a strong positive correlation was obtained between Fe, Mn, As, Zn, Cu, Ni, Ca, and Cd elements and TOC and TN. The Mn/Fe ratio revealed a long-term redox and acidic condition at Bera Lake. Geoaccumulation index for all individual metals has classified Bera Lake sediment as low to moderately polluted. However, elemental values when compared with thresholds limits of SQG indicated that Bera Lake sediments were contaminated by arsenic and iron. Results prove that deforestation during the five phases of land developments since 1972 has significantly contributed to the existence of metals fluxes into the area.